Minat dan Pengetahuan Generasi Z Serta Milenial dalam Berinvestasi di Pasar Modal Syariah: Analisis Bibliometrik - Dewangga Wibiantoro, Awang; Slamet Budi Hariyanto; Eko Sujianto, Agus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The country of Indonesia, with a predominantly Muslim society, provides a platform for its people to make investments which are of course in accordance with basic sharia principles, namely in the sharia capital market. However, it’s known that not many young people have sufficient literacy or knowledge about the world of investment, especially sharia investment. Many articles have been published discussing the topic of sharia investment. Because of that, this research was conducted with the aim of identifying the existence of published articles discussing sharia investment in 2019 - 2023. The method applied is the bibliometric method, with a sample of 31 articles from journals indexed by Sinta. The objects used in this research are the younger generation such as generation z and millennials. The results obtained that sharia investment is one of the trending topics discussed in 2022. And starting from 2019 - 2022, this topic will experience an increase in publications in sharia economic journals. This topic is mostly published in journals indexed by Sinta 4 or Sinta 5 with 12 articles each. Most of these articles state that knowledge actually has a direct and significant effect on interest in investing in the Islamic capital market